Molecular Detection of Azole-Resistant Aspergillus fumigatus in Clinical Samples - Buil, Jochem B.; Zoll, Jan; Verweij, Paul E.; Melchers, Willem J. G. (Frontiers in Microbiology, 2018)
Aspergillus diseases are often caused by Aspergillus fumigatus. Azoles are the mainstay of therapy, but the management of aspergillosis is hampered by the emergence of azole resistance. Rapid detection of azole resistance might benefit treatment outcome by early treatment modifications. However, the yield of fungal culture in invasive aspergillosis is low and susceptibility testing requires several days to be completed. To overcome the low yield of fungal cultures and slow detection of resistance, it is possible to use molecular tools directly on clinical specimens in order to rapidly detect molecular markers of azole resistance. Molecular tools to detect resistant markers in the Cyp51A gene can be expected to be less sensitive compared to molecular tools to detect Aspergillus DNA as the Cyp51A gene is a single copy gene and the target for Aspergillus DNA is often a multi-copy gene. In this review, we summarize the current molecular tools for detection of azole-resistant A. fumigatus directly in clinical material. Several in-house PCR assays have been applied directly on clinical material. Furthermore, two assays are commercial available; the AsperGenius and MycoGENIE. The amplification of resistance markers was successful in 70 to 100% of samples that were positive for Aspergillus DNA in BAL samples using the AsperGenius assay. Despite using several samples per patient, amplification of resistance markers was only successful in 33% to 57% of patients with Aspergillus DNA in blood. Furthermore, several sequence based methods have been applied with the benefit of the ability to detect other Cyp51A gene alterations.